Migration and its effects in Türkiye and the world - GÜRDER, FİLİZ (Akademisyen Kitabevi, 2023)
People have always migrated. The history of mankind is also a history of migration. Global migration, i.e. intercontinental mobility, has existed since the beginning of colonialism. It is estimated that from the dawn of colonialism in the 1500s to the industrial age of 1914, more than 100 million people participated in large and long migrations or were sold (Atlas of Migration, 2020). The number of international migrants worldwide, which was 153 million in 1990, has risen to more than 280 million worldwide by mid-2020. At the end of 2021 alone, the United Nations High Commissioner for Refugees (UNHCR) counted around 89.3 million people displaced from their homes, 53.2 million of whom were internally displaced. Refugees fleeing the war in Ukraine are not included in these statistics (Statista 2022). Today every modern society and every state is a result of this mobility.Migration affects almost every country in the world. Migration processes and consequences know no borders, status, territories or forms of government. It encompasses more people, actors and countries than ever before. Migration is a transnational phenomenon and no country can solve problems alone. For this reason, it is helpful to know the numbers and impact of migration on the world and countries. On the other hand, it is necessary to clarify the current conceptual confusion. Crowds of immigrants are referred to by terms such as immigrant, asylum seeker, refugee, and foreigner. However, the legal status of these terms differs from each other.This study aims to see the dimensions and impact of this high number of migrations while the influx of refugees continues in the world and in Turkey in particular. In the study, the data collected through document analysis, one of the qualitative research techniques, was analyzed through a descriptive analysis method. Documents examined from international sources contain data for 2020 and 2021. Examining the causes of migration shows that there is usually flight from war and terror, hope for prosperity, traditions and changing borders. A comparison of the country\"s own population with the number of immigrants taken in shows that the countries that take in the highest proportion of refugees are the neighboring countries of Syria. From around the world, it can be seen that the largest migration in recent years has been from Mexico to the United States, while the largest migration in the rest of the world has been from Syria to Turkey. For several years, Turkey has continued to be the country that receives the most immigrants in the world. According to official figures, around 4 million refugees and asylum seekers are living in Turkey at the end of 2021, which has been struggling with increasing difficulties in recent years. Even if it was initially assumed that the refugees who had immigrated were temporary people, over time this process has developed into a permanent provisional arrangement. Most of these refugees and asylum seekers come from Syria. About 300,000 refugees and asylum seekers are of other nationalities, mainly from Afghanistan, Iraq and Iran. One in 23 people living in Turkey left their country and immigrated (Statista, 2022). Refugee means financial and social transfer. Financial and social transfers by immigrants pose both risks and opportunities. The high number of refugees means increasing pressure on resources and infrastructure in Turkey.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Yönetim Bilişim Sistemleri; Social Sciences and Humanities; Management; Management Information Systems; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities